The Influence of Spirituality in the Workplace, Personality, and Organizational Commitment of Employees on the Mental Well-Being of Employees at the East Java I Regional Tax Office - Agung Mulyo Harjo; Purwanto Purwanto; Sri Rahayu (Neo Journal of economy and social humanities, 2026)
This study examines the influence of workplace spirituality, personality, and organizational commitment on employee mental well-being at the East Java I Regional Tax Office. Using a quantitative approach with a causal associative design, this research involved a census of 180 employees. Data were collected through structured questionnaires measured on a five-point Likert scale and analyzed using multiple linear regression with SPSS version 20. Workplace spirituality was measured through meaningful work, sense of community, and value alignment; personality was assessed based on the Big Five dimensions; organizational commitment comprised affective, continuance, and normative components; and mental well-being encompassed emotional, psychological, and social well-being. The results indicate that workplace spirituality, personality, and organizational commitment each have a positive and significant effect on employee mental well-being. Simultaneously, all independent variables significantly influence mental well-being, demonstrating strong explanatory power of the proposed model. This study extends prior research by integrating these psychological and organizational factors within a Positive Organizational Behavior framework in a high-pressure public tax institution context. The findings offer practical implications for public sector management, particularly in designing workplace spirituality initiatives, strengthening affective commitment, and supporting employees’ psychological resilience to sustain mental well-being in demanding organizational environments.